THE EFFECT OF SOCIAL INTERACTIVE WRITING METHOD ON THE STUDENT’S WRITING COMPETENCY AT EIGHTH GRADE OF SMP NEGERI 3 SAWAN IN THE ACADEMIC YEAR 2013/2014 - Hasri, Putu Perwita; Marhaeni, A. A. Istri Ngurah; Dewi, Ni Luh Putu Eka Sulistia (Jurnal Pendidikan Bahasa Inggris undiksha, 2018)
This study aimed at investigating the effect of Social Interactive Writing Method on the students’ writing competency. Randomized Posttest-Only Control Group Design was applied in this study which consists of 56 students. The instruments were analyzed descriptively and inferentially. The result of the analysis shows that the students who were taught by using Social Interactive Writing Method better than the students who were taught by using Conventional Method. It had been proven from the mean score was 87.64 while the control group was 67.92. Furthermore, from the analysis by using inferential statistic, it was found that the value of t observed (tob) was 12.012. It was higher than t critical value (tcv) which was 1.64 (ɑ = .05). After comparing t observed and t critical value, it was clear that t observed (tob) exceeded t critical value (tcv). In conclusion, the alternative hypothesis was accepted. Therefore, it could be confirmed that the application of Social Interactive Writing Method gave significant effect toward students’ writing competency. Keywords: Social Interactive Writing Method, Writing competency